A low-cost smart parking solution for smart cities based on open software and hardware - Fernandes, J.; Serrão, C.; Garrido, N. (INTSYS 2018 - 2nd EAI International Conference on Intelligent Transport Systems, 2018)
Traffic management and car parking on modern cities continues to be a problem both for citizens and for city officials. The increasing number of vehi- cles flowing into the city drain the existing scarce parking resources, and the in- crease in time spent looking for a parking spot leads to more congestions, para- sitic traffic, whilst augmenting fuel consumption and air pollution. In this paper we present an integrated flexible solution developed to help address this issue, using open hardware and software components to develop a low-cost smart park- ing system suitable for contemporary metropolitan cities. The smart parking so- lution is based on Arduino boards for the sensors network and on Raspberry Pi single-board computers for the gateway devices, integrated through specific de- veloped software components and a mobile application for the end-users.